1992
DOI: 10.1177/004051759206200806
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Cotton Fabrics Crosslinked with Different Molecular Chain Lengths of Aldehyde Agents

Abstract: Cotton fabric has been crosslinked with differing molecular chain lengths of an aldehyde crosslinking agent (formaldehyde and glutaraldehyde). The formaldehyde treated fabric shows lower tensile strength retention than the glutaraldehyde treated fabric but higher elongation retention for a given agent concentration. At the same dry or wet crease recovery angle, tensile strength of the formaldehyde treated fabric is lower than that of the glutaraldehyde treated fabric, but elongation is higher. Wet crease recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Our previous studies [ 16] showed that the physical properties of dimethylolethyleneurea (DMEU) treated fabrics were significantly different from those of dimethylol-N,N'-dimethylene-tris-ethyleneurea (DMDME3EU), and revealed the higher tensile strength retention of fabrics treated with DMDME3EU at the same dry and wet crease recovery angles. Other studies [ 1,10,14] mentioned that the longer crosslinking agent yielded better physical properties and a larger pore structure of the treated fabrics than the shorter crosslinking agent. Ber-toniere et al [3] pointed out that the degree of agent spreading in cotton fabric is different for differing molecular chain lengths of crosslinking agents.…”
mentioning
confidence: 97%
“…Our previous studies [ 16] showed that the physical properties of dimethylolethyleneurea (DMEU) treated fabrics were significantly different from those of dimethylol-N,N'-dimethylene-tris-ethyleneurea (DMDME3EU), and revealed the higher tensile strength retention of fabrics treated with DMDME3EU at the same dry and wet crease recovery angles. Other studies [ 1,10,14] mentioned that the longer crosslinking agent yielded better physical properties and a larger pore structure of the treated fabrics than the shorter crosslinking agent. Ber-toniere et al [3] pointed out that the degree of agent spreading in cotton fabric is different for differing molecular chain lengths of crosslinking agents.…”
mentioning
confidence: 97%
“…Most researchers have focused on glyoxal as a durable press finishing agent, with Lewis acids such as magnesium chloride and aluminum chloride as the catalysts [4,12]. Glutaraldehyde for crosslinking cotton was included in some of the early studies [1][2][3]8], but a systematic investigation of glutaraldehyde as a crosslinking agent has not been reported.…”
mentioning
confidence: 99%